Integration of the Unified Theory of Acceptance and Use of Technology Model in Acceptance of E-Learning at State Islamic Religious Universities in East Java - Ilham Ilham; Merlin Apriliyanti (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme)
This study aims to identify the variables from the Unified Theory of Acceptance and Use of Technology (UTAUT) model that influence e-learning acceptance among lecturers at State Islamic Religious Universities (PTKIN) in East Java. Employing a quantitative approach with a cross-sectional design, the study tested a theoretical model using hypothesis-driven analysis. Data were collected through online questionnaires with a simple random sampling technique, involving 321 lecturers as respondents. Responses were measured using a five-point Likert scale, and Structural Equation Modeling (SEM) was used for data analysis. The findings show that effort expectancy, facilitating conditions, hedonic motivation, habits, and behavioral intentions significantly influence lecturers’ acceptance of e-learning. Conversely, performance expectancy and social influence do not show significant effects. Behavioral intention also mediates the positive effect of facilitating conditions and habits on actual e-learning use. Although this study focuses on two PTKIN institutions in East Java, limiting generalizability, it provides useful insights for higher education management. The results have practical implications for designing effective strategies and policies to enhance e-learning adoption, such as lecturer training, awareness campaigns, periodic system reviews, and supportive policy development. E-learning offers solutions to overcome limitations of conventional teaching and enhances access, monitoring, and skill development, contributing to the improved performance of PTKIN. This research also validates the UTAUT model in a new cultural and institutional setting, expanding its relevance for future studies on technology acceptance in education.